Pengembangan Modul Pembelajaran dalam Meningkatkan Hasil Belajar Mahasiswa: Tinjauan Kepraktisan dan Keefektifan - Muh. Rafi'y; Zahratul Qolbi (Journal Education Innovation (JEI), 2023)
This research is development research (R&D) which aims to develop learning modules in integrated learning courses. From the practical validity test carried out, it was found that this module was categorized as good and suitable for use. And after implementation and evaluation tests, the results were obtained in the form of effective teaching modules in improving the learning outcomes of Musamus University PGPAUD students. The data collected was obtained from assessments by material experts, media experts, student response questionnaires and posttest student learning outcomes. The data analysis techniques used are descriptive quantitative and qualitative. So the conclusion is that the learning module developed has met the valid and practical criteria and has been implemented and is effective in improving student learning outcomes in the PGPAUD department at Musamus University